Efeitos do manganês sobre respostas neurocomportamentais e bioquímicas em peixe-zebra (Danio rerio) - Ferreira, Sabrina Antunes (2022)
Manganese (Mn) is considered a important environmental pollutant, as well as a putative risk factor for neurodegenerative disorders. As the 12° most abundant element and comprising aproximattly 0,1% of the earth surface, Mn is omnipresent in the environment. As an essential element, it is crucial for the function of a variety of enzimes. As such, Mn is involved in aminoacids, lipids, proteins and carbohydrates metabolism. Considering Mn dual role, it is extremely important to carry out toxicological studies that investigate the limits between the functional and toxicological window of exposure to the element in biological systems. Little is known about the effects that this contaminant can cause when in environmentally relevant concentrations and occurrences. Therefore, using zebrafish, this study aimed to verify behavioral changes and locomotor deficits associated with psychiatric disorders, namely anxiety phenotypes, generated by exposure to Mn. Zebrafish were exposed to MnCl2 in 0.5, 2.0, 7.5 e 15.0 mg/L by 96 h. In order to find biomarkers after Mn expousure, we measured the activity of AChE enzime and the cortisol levels. Furthermore, the brain tissue Mn content was quantified. Through behavioral tests, we discovered that Mn expousure, along with locomotor deficits, induced anxiety-like fenotypes in zebrafish. High concentrations caused cell viability loss, higher Mn accumulation, higher AChE activity in the brain tissue, and higher levels of cortisol content in whole-body samples. Our findings show that zebrafish are quite sensitive to Mn levels found in the environment. In summary, we demostrate that Mn expousure can lead not only to behavioral alterations, but also to psychiatric alterations, namely anxiety.